Consumer's intention of purchase sustainable products: the moderating role of attitude and trust - Hosseinpour, Masoumeh; Nezakati, Hossein *; Sidin, Samsinar Md; Yee, Wong Foong (Global Strategic Management Inc., 2016)
Awareness about environment has found its place in consumer's mind set. During the past decades, consumers considered issues such as environmental issues and social issues (e.g. label's right or child's right) while purchasing products. Hence, this group of consumers are looking forward the alternative products such as sustainable products which could be presuming environmental issues and social issues. Sustainability is a vital element which is a challenge for product developers nowadays. On the other hand, companies put efforts to meet the demand of this group of consumers where the competition is high. While, there are available sustainable products in the markets, consumer's intention of purchase these products is imprecise. Besides, the attributes of these products are not categorised yet by scholars. Therefore to understand consumer's intention, the present study aims (i) to categorise the sustainable products; (ii) to extract the influential factors on consumer's intention to purchase sustainable products; and (iii) to develop a conceptual model of consumer's intention to purchase sustainable products. By reviewing literature, the factors of belief, knowledge, attitude, company's sustainable responsibility (i.e. economic, environment and social), trust and perceive quality are founded to be as the influential factors on consumer's intention to purchase these products. Besides, the mediating roles of attitude and trust on consumer's intention to purchase sustainable products are considered in this paper. Eventually, the conceptual framework of consumer's intention to purchase sustainable products is proposed.